Rawls's Dangerous Idea?: Liberalism, Evolution and the Legal Requirement of Religious Neutrality in Public Schools - Beckwith, Francis (Journal of law and religion, 2005)
Since the mid-1990s the debate over the teaching of evolution in public schools has acquired new life, largely as a result of a new generation of critics of evolution. In comparison to their predecessors, today's critics are better credentialed, have published works with respected academic and university presses and periodicals including peer-reviewed ones, and offer much more sophisticated arguments. The purpose of this essay, however, is not to engage the scientific merits of the arguments offered by these maverick scholars. Rather, the purpose of this essay is to explore a problem of jurisprudence, raised by philosopher Alvin Plantinga and responded to by philosopher of science Robert T. Pennock, whose resolution has relevance to the constitutional question of whether the teaching of evolution along with the works of its critics is permissible in a society whose citizens embrace contrary philosophical and religious points of view.